L’impact des interventions de développement sur la prise de décision à migrer des jeunes en Afrique Occidentale. Le Projet MIGCHOICE Senegal - Zingari, Guido Nicolas; Cissokho, Dramane; Riccio, Bruno; Sakho, Pape (Antropologia Pubblica, 2024)
This article stems from ethnographic research focused on the development-migration nexus in different Senegalese contexts: Louga, Diaobé, Dakar, Thiès and the Saloum Islands. The impact of interventions in terms of development and migration depends on a multitude of local and international actors, micro-projects and public-private partnerships, as well as on the presence of more or less dense migration networks. The underemployment of young people, deagrarianisation, and other phenomena are intertwined with a growing criminalisation of displacement and an irregularisation of international migration. The relationships among mobility-restriction regimes, the disappointing impact of development interventions, and the individualized way in which people represent their lived (im)mobilities affect migration choices in all three contexts.